2019
DOI: 10.1089/vbz.2018.2317
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Listeria ivanovii Strains in Wild Rodents in China

Abstract: Listeria is ubiquitous in natural environments and can be isolated from animal hosts, including rodents. Listeria ivanovii and Listeria monocytogenes are the main pathogenic species that can cause serious listeriosis in animals and human. In this study, we investigated the prevalence of Listeria in wild rodents from six regions in China, and analyzed the molecular characteristics and antibiotics resistance of the L. ivanovii isolates. A total of 702 fecal samples of 25 different species of wild rodents were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Interestingly, L. seeligeri was not encountered among our bear isolates. Similarly, L. ivanovii accounted for many of the Listeria isolates from rodent surveys in China (Wang et al, 2017;Cao et al, 2019), but was not encountered in our study.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Interestingly, L. seeligeri was not encountered among our bear isolates. Similarly, L. ivanovii accounted for many of the Listeria isolates from rodent surveys in China (Wang et al, 2017;Cao et al, 2019), but was not encountered in our study.…”
Section: Discussionmentioning
confidence: 61%
“…The prevalence of L. monocytogenes in our study (36%) was noticeably higher than in most other wildlife surveys, where prevalence ranged from 0.3% to 18% (Hayashidani et al , ; Lyautey et al , ; Wacheck et al , ; Nowakiewicz et al , ; Weindl et al , ; Wang et al ., ; Cao et al , ;). Only two wildlife studies, involving urban birds in Finland and France, respectively, yielded prevalence levels of 33–36% (Bouttefroy et al , ; Hellstrom et al , ), similar to what we found in the bears.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have noted that wild rodents and pikas in China carried various STs of L. ivanovii subsp. ivanovii, and the predominant sequence types were ST1 and ST2 (12,13). ST1 strains were collected from five species of wild rodents in Tibet and Yunnan province, which reveals the potential ability of ST1 clonal strains to spread cross species and regions (13).…”
Section: Discussionmentioning
confidence: 98%
“…A total of 116 L. ivanovii subsp. ivanovii strains were isolated from intestinal contents of wild rodents from 12 provinces in China during 2014-2016 (12,13). The strains belong to five sequence types (STs), and the predominant subtypes were ST1 (10/116, 8.62%) and ST2 (100/116, 86.21%).…”
Section: Introductionmentioning
confidence: 99%